Developmental toxicity of the fungicide ziram in zebrafish (Danio rerio) - Cao, Fangjie; Souders, Christopher L; Li, Pengfei; Adamovsky, Ondrej; Pang, Sen; Qiu, Lihong; Martyniuk, Christopher J (Chemosphere, 2019)
Ziram is a broad spectrum pesticide that belongs to the class of dimethyl-dithiocarbamate (DTC) fungicides. The objectives of this study were to assess the effects of ziram in developing zebrafish. Ziram was highly toxic to zebrafish embryos, with a 96-h LC50 value of 1082.54 nM (∼0.33 mg/L). Zebrafish embryos at 6 h post-fertilization (hpf) were exposed to solvent control (0.1% DMSO), or one dose of 1, 10, 100, and 1000 nM ziram for 96 h. Ziram induced lethality in a dose-dependent manner, decreased hatching rate and heartbeat, and caused wavy deformities at 72 and 96 hpf at 100 and 1000 nM. Basal oxygen consumption rates of zebrafish at 24 hpf were decreased with 1000 nM, suggesting that ziram affects oxidative phosphorylation. We also measured the expression of transcripts associated with the oxidative stress response (sod1 and sod2) and dopamine receptor signaling at ∼96 h of exposure. There was no difference in the expression of genes related to oxidative stress, nor those related to the dopamine system. Locomotor activity was also assessed in larval zebrafish (7 dpf), and ziram increased total activity, the velocity in light zone, and total distance moved at 10 nM, while it decreased the mean time spent in the dark zone at 1 and 10 nM. Behavioral responses were dependent upon the time point and clutch examined. These data demonstrate that ziram negatively impacts embryonic development (i.e. mortality, hatching, heartbeat and notochord development) of zebrafish, decreases basal respiration of embryos, and alters behavioral responses in larvae.
Keywords: Fungicides, Industrial; Oxidative Stress; embryo nesavčí; Ziram; dopamin; oxidační stres; chování zvířat; Embryo, Nonmammalian; lokomoce; embryonální vývoj; Oxygen Consumption; larva; průmyslové fungicidy; dánio pruhované; zvířata; Embryonic Development; Zebrafish; ziram; spotřeba kyslíku; Dopamine; Larva; Locomotion; Animals; Behavior, Animal